The effect of family support on the rehabilitation of patients with spinal cord injury - Rinawati Tarigan; Mona Hastuti (Journal of Midwifery and Nursing, 2023)
Spinal cord injury is a serious and complex medical condition that affects many aspects of a patient's life. This study aims to explore the influence of family support on the rehabilitation process of patients with spinal cord injury. Through a survey involving various respondents who have experienced spinal cord injury, this study attempts to identify how family support, both in the form of emotional and physical support, can affect patients' motivation, quality of life, and their rehabilitation outcomes. The survey results showed that the majority of respondents felt positively supported by their families, which had a positive impact on patient motivation and their quality of life. Family involvement in medical care and creating an appropriate environment also proved important in the rehabilitation process. However, the study also revealed that conflicts within the family can be an obstacle in providing effective support. The results of this study highlight the importance of the family's role in the recovery of patients with spinal cord injury and its practical implications in healthcare. With a better understanding of the positive influence of family support, health and care providers can design more effective interventions to improve the rehabilitation process of patients. This study also provides a basis for further research in understanding more in-depth aspects of family support in the context of spinal cord injury. With collaborative efforts between the patient, family, and healthcare team, patients with spinal cord injury have a better chance of achieving optimal recovery and improving their quality of life.